2019
DOI: 10.1038/s41598-019-41678-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane insertion and secretion of the Engrailed-2 (EN2) transcription factor by prostate cancer cells may induce antiviral activity in the stroma

Abstract: Engrailed-2 (EN2) is a homeodomain-containing transcription factor that has roles in boundary formation and neural guidance in early development, but which is also expressed in a range of cancers. In addition to transcriptional regulation, it is secreted by cells and taken up by others through a mechanism that is yet to be fully elucidated. In this study, the distribution of EN2 protein in cells was evaluated using immunofluorescence with a set of antibodies raised against overlapping epitopes across the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, we did not see such correlation in our panel of cell lines, suggesting that even though IFNs are major regulatory factors of MX2, there are also other mechanisms involved. For instance, a recent study by Punia et al found that Engrailed‐2 (EN2) transcription factor secreted by prostate tumors can induce MX2 expression in stromal cells (Punia, Primon, Simpson, Pandha, & Morgan, ), and MX2 was a single gene showing a dose–response relationship to recombinant EN2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not see such correlation in our panel of cell lines, suggesting that even though IFNs are major regulatory factors of MX2, there are also other mechanisms involved. For instance, a recent study by Punia et al found that Engrailed‐2 (EN2) transcription factor secreted by prostate tumors can induce MX2 expression in stromal cells (Punia, Primon, Simpson, Pandha, & Morgan, ), and MX2 was a single gene showing a dose–response relationship to recombinant EN2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…During the development of mouse, EN1 and EN2 have overlapping functions in regulating formation of additional fissures and for extensive cerebellar growth [8,9], but mutations in EN1 and EN2 produce different phenotypes [10]. In humans, aberrant expression of these genes has been associated with the pathogenesis of many types of tumors, including breast cancer [11,12], prostate cancer [13,14], colorectal cancer [15], and ovarian cancer [16,17]. Elevated EN2 expression in particular has been associated with poor survival, and this gene has been proposed as a biomarker for breast cancer screening [18].…”
Section: Introductionmentioning
confidence: 99%
“…EN2 is a homeodomain-containing transcription factor that has an essential function in early development, which in mammals includes the delineation of the midbrain/hindbrain border [ 24 ]. For a transcription factor it has a number of unusual properties, including the ability to be secreted from cells and taken up by others [ 25 ]. Indeed, a recent study indicated that prostate cancer cells can secrete EN2 protein through vesicles which are then taken up by other non-EN2 expressing cells, where it can directly influence the transcription of target genes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For a transcription factor it has a number of unusual properties, including the ability to be secreted from cells and taken up by others [ 25 ]. Indeed, a recent study indicated that prostate cancer cells can secrete EN2 protein through vesicles which are then taken up by other non-EN2 expressing cells, where it can directly influence the transcription of target genes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%